Influence of Altered Microbes on Soil Organic Carbon Availability in Karst Agricultural Soils Contaminated by Pb-Zn Tailings - Li, Qiang; Liu, Chang; Wang, Xiaohong; Jin, Zhenjiang; Song, Ang; Liang, Yueming; Cao, Jianhua; Müller, Werner E. G. (Frontiers in Microbiology, 2018)
Soil organic carbon (SOC) availability is determined via a complex bio-mediated process, and Pb-Zn tailings are toxic to the soil microbes that are involved in this process. Here, Pb-Zn-tailings- contaminated karst soils with different levels (paddy field>corn field>citrus field>control group) were collected to explore the intrinsic relationship between Pb-Zn tailings and microbes due to the limited microbial abundance in these soils. The SOC concentration in the paddy fields is the highest. However, based on the soil microbial diversity and sole-carbon-source utilization profiles, the rate of SOC availability, McIntosh index, Shannon-Wiener diversity index, Simpson's diversity index and species richness are the lowest in the rice paddy soils. According to the results of Illumina sequencing of the 16S rRNA gene, Acidobacteria and Proteobacteria are the dominant phyla in all samples, accounting for more than 70% of the reads, while the majority of the remaining reads belong to the phyla Verrucomicrobia, Chloroflexi, Actinobacteria, Bacteroidetes and Nitrospirae. We also observed that their class, order, family, genus and operational taxonomic units (OTUs) were dependent on SOC availability. Pearson correlation analysis reveals that L-asparagine utilization profiles show significant positive correlation with OTUs 24, 75 and 109 (r=0.383, 0.350 and 0.292, respectively), and malic acid utilization profiles show significant positive correlation with OTUs 4, 5, 19, 27 (Bradyrhizobium), 32 (Burkholderia), 75 and 109 (r=0.286, 0.361, 0.387, 0.384, 0.363, 0.285 and 0.301, respectively), as also evidenced by the redundancy analysis (RDA) biplot and heat map. These results indicate that the most abundant groups of bacteria, especially the uncultured facultative Deltaproteobacteria GR-WP33-30 (OTU 24), after long-term acclimation in heavy metal-contaminated soil, are associated with the variance of labile carbon source such as L-asparagine and may have considerable control over the stability of the vast SOC pool in karst surface soils with different agricultural land-use practices. These findings can expand our understanding of global soil-carbon sequestration and storage via changes in microbial community structure of the most abundant species.